แนวปฏิบัติเพื่อส่งเสริมการปฏิบัติงานและความพึงพอใจของพนักงานมหาวิทยาลัยศิลปากร วิทยาเขตพระราชวังสนามจันทร์ - จิตต์จรัส, ศิริณา; ปุณยบุรณะ, อรอุษา (Ganesha Journal, 2017)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาระดับการปฏิบัติงานและระดับความพึงพอใจของพนักงานมหาวิทยาลัยศิลปากร วิทยาเขตพระราชวังสนามจันทร์ 2) เปรียบเทียบความแตกต่างระหว่างความพึงพอใจของพนักงานมหาวิทยาลัยศิลปากร จำแนกตามข้อมูลทั่วไป คณะ และประเภทสายงาน และ 3) เพื่อเสนอแนวทางการส่งเสริมการปฏิบัติงานของพนักงานมหาวิทยาลัยศิลปากร กลุ่มตัวอย่างได้แก่พนักงานมหาวิทยาลัยใน 5 สังกัดคณะวิชาประกอบด้วยคณะเภสัชศาสตร์จำนวน 20 คน วิศวกรรมศาสตร์และเทคโนโลยี จำนวน 19 คน คณะอักษรศาสตร์ จำนวน 18 คน คณะศึกษาศาสตร์ จำนวน 17 คน และวิทยาศาสตร์ จำนวน 12 คน รวมทั้งหมด 86 คน และเก็บรวบรวมข้อมูลเชิงปริมาณ โดยใช้แบบสอบถามชนิดมาตราส่วนประมาณค่า 5 ระดับ สอบถามความพึงพอใจในด้านปัจจัยแรงจูงใจ (Motivational Factors) และปัจจัยอนามัย (Hygiene Factors)ส่วนระดับการปฏิบัติงานใช้ผลการปฏิบัติงานตามเกณฑ์ที่มหาวิทยาลัยกำหนดทั้งสายวิชาการสายบริหารและการปฏิบัติงานทั่วไป สถิติที่ใช้ในการวิเคราะห์ข้อมูลคือค่าร้อยละ ค่าเฉลี่ยค่าเบี่ยงเบนมาตรฐาน การสัมภาษณ์กลุ่มและรายบุคคล จำนวน 20 คน เกี่ยวกับแนวส่งเสริมการปฏิบัติงาน ส่วนการเก็บรวบรวมข้อมูลเชิงคุณภาพโดยกลุ่มเป้าหมาย สรุปผลการวิจัย 1. ระดับการปฏิบัติงานของพนักงานมหาวิทยาลัยอยู่ในระดับดี จำนวนร้อยละ 18.60ระดับคะแนนรองลงมาคือ ระดับพอใช้ และระดับปรับปรุง (ต่ำกว่า 3) มีจำนวนเท่ากันคือร้อยละ16.28 ส่วนระดับดีมาก และระดับดีเด่น ร้อยละ 5.81 และ 4.65 ตามลำดับ 2. ระดับความพึงพอใจของพนักงานอุดมศึกษาในภาพรวมอยู่ในระดับมากทั้ง 10 ด้านเมื่อพิจารณาเป็นรายด้านพบว่า มีความสอดคล้องกับภาพรวมคือมีความพึงพอใจอยู่ในระดับมากเช่นกัน ยกเว้นด้านเงินเดือนและผลประโยชน์เกื้อกูลและสภาพแวดล้อมในการทำงานมีค่าอยู่ในระดับปานกลาง 3. การเปรียบเทียบระดับความพึงพอใจ จำแนกตามคณะวิชาพบว่า คณะเภสัชศาสตร์มีความพึงพอใจแตกต่างจากคณะอักษรศาสตร์ และคณะวิทยาศาสตร์ ส่วนพนักงานจำแนกตามประเภทสายงานพบว่ามีค่าเฉลี่ยความพึงพอใจระหว่างพนักงานสายวิชาการ และสายบริหารฯแตกต่างกันอย่างมีนัยสำคัญที่ระดับ .05 การเปรียบเทียบระดับความพึงพอใจของพนักงานจำแนกตามเพศ อายุ การศึกษา และประสบการณ์การปฏิบัติงานพบว่า มีค่าเฉลี่ยความพึงพอใจไม่แตกต่างกัน 4. แนวการปฏิบัติเพื่อส่งเสริมการปฏิบัติงานและความพึงพอใจของพนักงานมหาวิทยาลัยควรพิจารณาส่งเสริมด้านเงินค่าตอบแทน สวัสดิการบ้านพัก ลดภาระงานอื่นๆปรับเพิ่มงบประมาณการศึกษาอบรม ส่งเสริมการทำวิจัย สายบริหารควรมีความโปร่งใสในการบริหารงานทั้งผลประโยชน์ การประเมินผล และให้มีการจัดการความรู้การประกันคุณภาพอย่างต่อเนื่อง GUIDELINE TO ENHANCE JOB PERFORMANCE AND JOB SATISFACTION AMONG CONTRACTED UNIVERSITY’S EMPLOYEE OF SILPAKORN UNIVERSITY, SANAMCHANDRA PALACE CAMPUS The objectives of this research were to 1) study job performance and job satisfaction of contracted university’s employees of Silpakorn University, Sanamchandra Palace campus 2) compare job satisfaction of Silpakorn University officers according to general data, faculty and work line. 3) to enhance guideline of contracted university’s employee of Silpakorn University, Sanamchandra Palace campus. The samples were contracted university’s employees of Silpakorn University, Sanamchandra Palace campus who had been working at five faculties of Silpakorn University. The samples consisted of 20 employees from Faculty of Pharmacy, 19 employees from Faculty of Engineering and Technology, 18 employees from Faculty of Arts, 17 employees from Faculty of Education and 12 employees from Faculty of Science; Total 86 employees. This research instruments were five valuation scale questionnaire for motivational and hygiene factors. For job performance used job performances evaluation that ruled by Silpakorn University and used in academic, administration and general work line and reliability was at .97. Statistics for data were analyzed by using frequency, percentage, mean, standard deviation including group and individual interview about guideline that was qualitative data total 20 persons The findings revealed that : 1. Level overall job performance of Contracted University’s employees were in good level culmination of percentages were 18.60%, the second level was moderately and third level was need to improvement (lower than 3.00) that was similar to second level 16.28%; better level (4.00–4.49) and outstanding level Only 5.81% and 4.65% 2. Level Overall satisfactions of Contracted University’s employees were in high level in all 10 fields. Each of fields study revealed that related to overall image; either had high satisfaction level except salary and benefit including working circumstances were in average level. 3. Overall image comparison classified from each faculty found that Faculty of Pharmacy had different satisfaction from Faculty of Arts and Faculty of Science same as working types; had satisfaction mean in different level between academic and administration line at the 0.05 level of significance. Overall image comparison from regular data classified from gender, age, education and operational experience found that satisfaction mean is different without the level of significance. 4. The guideline should cogitate for promoting salary and residential welfare, decreasing duty, increasing educational and training budget and promoting research in administration. Moreover, the university should have revelation and good governance in administration and benefit management including appraisement and provide knowledge management process continually, it will be utilizable for organizations